Correction to: Medicinal plants used by women in Mecca: urban, Muslim and gendered knowledge - Afnan Alqethami; Julie A. Hawkins; Irene Teixidor-Toneu (BMC, 2017)
Abstract In the original publication [1] were the Arabic letters in Table 2 incorrect. The corrected version of Table 2 can be found as Additional file 1 in this Erratum.